Pig's blood in cigarette filters: how a single news release highlighted tobacco industry concealment of cigarette ingredients. Issue 2 (15th December 2010) - MacKenzie, Ross; Chapman, Simon
Abstract : The tobacco industry is not obligated to disclose ingredients and additives used in manufactured tobacco production. This paper describes global reaction to a press release highlighting evidence that porcine haemoglobin ("pig's blood") was sometimes used in cigarette manufacturing while never being disclosed to smokers. The case study illustrates the power of press releases to ignite major interest in tobacco control issues.